Elaboración de estructura organizacional y manual de funciones para el supermercado 'La Yapita' Atuntaqui, Imbabura - Quinatoa Donoso, Alvaro Isaias (2023)
The present work, it is based on the elaboration of the organizational structure and manual of functions for the supermarket 'la yapita', atuntaqui-imbabura', to comply with it, different objectives were determined, proposing to analyze the current organizational structure of the company, as well as also the determination of the different areas of operation, the design of the organizational structure according to the needs that the company requires and the design of a manual of functions according to the operational areas of the company. To comply with each of the objectives, the theoretical foundation of the research was structured, through the dependent and independent variables\; Likewise, in the methodology it will be through a non experimental study, using statistical data through an interview and survey of the personnel that works in the company, in which it was obtained that the supermarket needs the implementation of process manuals to determine the activities, functions and responsibilities within the different positions that make up the organization chart of the supermarket 'la yapita'.